Expression 11: "c" Subscript, 1 , Baseline equals "b" Subscript, "x" , Baseline minus "a" Subscript, "x" , Baselinec1=bx−ax
equals=
2.52.5
11
Expression 12: "c" Subscript, "d" , Baseline equals "a" Subscript, "x" , Baseline plus StartFraction, left parenthesis, "b" Subscript, "x" , Baseline minus "a" Subscript, "x" , Baseline , right parenthesis Over 2 , EndFractioncd=ax+bx−ax2
equals=
2.2 52.25
12
Δx = ${b_x} - ${a_x} = ${c_1} left parenthesis, "c" Subscript, "d" , Baseline , "f" left parenthesis, "a" Subscript, "x" , Baseline , right parenthesis minus 0.0 5 , right parenthesiscd,fax−0.05
Label:
equals=
left parenthesis, 2.2 5 , 0.4 5 , right parenthesis2.25,0.45
13
Expression 14: "d" Subscript, 1 , Baseline equals "b" Subscript, 1 , Baseline minus "a" Subscript, 1 , Baselined1=b1−a1
equals=
1.2 51.25
14
Expression 15: "d" Subscript, 2 , Baseline equals StartFraction, left parenthesis, "b" Subscript, 1 , Baseline minus "a" Subscript, 1 , Baseline , right parenthesis Over 2 , EndFractiond2=b1−a12
equals=
0.6 2 50.625
15
Δy = ${b_1} - ${a_1} = ${d_1} left parenthesis, "b" Subscript, "x" , Baseline plus 0.0 5 , "a" Subscript, 1 , Baseline plus "d" Subscript, 2 , Baseline , right parenthesisbx+0.05,a1+d2
Label:
equals=
left parenthesis, 3.5 5 , 1.1 2 5 , right parenthesis3.55,1.125